Influence of water injection on broadband noise and hydrodynamic performance for a NACA66 (MOD) hydrofoil under cloud cavitation condition. (October 2021) - Wang, Wei; Li, Zhijian; Liu, Mingyu; Ji, Xiang
Abstract: Cavitation and its induced noise have negative effects on the hydrodynamic performance of underwater devices such as marine propellers. In this paper, a new flow control method of water injection is proposed to investigate its influence on the flow field around NACA66 (MOD) hydrofoil under the condition of cloud cavitation (Cavitation number σ = 0.83, Reynolds number Re = 5.1 × 10 5 ). The density corrected turbulence model (DCM) combined with Zwart-Gerber-Belamri cavitation model (ZGB) is used to simulate the hydrodynamic performance and the pressure fluctuation, while the dipole noise and quadrupole noise are calculated by Broadband noise source models. The numerical results are in good agreement with our previous experimental observations. The results are all compared with those for the original hydrofoil without water injection and show that the injected water noticeably weakens the severe pressure fluctuation on the hydrofoil suction surface and reduce the volume of cavitation by 72.89%. The water injection also performs well on drag reduction, which reduces the drag coefficient by 17.9%. The dipole noise on the hydrofoil surface is effectively suppressed, and the Curle Acoustic Power (AP) for over 50 dB is decreased by 28.99%. It is also found that the water injection significantly reduces the region of over 45 dB for Proudman AP by 46.21%. The water injection improves the stability of the flow field by means of providing extra energy, blocking the re-entrant jet, hindering the evolution process of turbulence and weakening the impact of the fluid on the hydrofoil wall.